Answer:
x = 10
Explanation:
Simplifying
8x + -3 = 6x + 17
Reorder the terms:
-3 + 8x = 6x + 17
Reorder the terms:
-3 + 8x = 17 + 6x
Solving
-3 + 8x = 17 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
-3 + 8x + -6x = 17 + 6x + -6x
Combine like terms: 8x + -6x = 2x
-3 + 2x = 17 + 6x + -6x
Combine like terms: 6x + -6x = 0
-3 + 2x = 17 + 0
-3 + 2x = 17
Add '3' to each side of the equation.
-3 + 3 + 2x = 17 + 3
Combine like terms: -3 + 3 = 0
0 + 2x = 17 + 3
2x = 17 + 3
Combine like terms: 17 + 3 = 20
2x = 20
Divide each side by '2'.
x = 10
Simplifying
x = 10